Historical Analysis of Changes in the Social Structure of Sago Farmers in the Traditional Community - Fajar Sidiq Limola; Ida Liana Tanjung; Rafika Hayati (Journal La Sociale, 2026)
This research examines the transformation of the social structure of sago farmers among the To Limola Indigenous community in Sassa Village, Baebunta Subdistrict, North Luwu Regency. Sago functions not only as a primary food source but also as a crucial element of the local social and cultural system. However, modernization, agrarian policies, and market penetration have significantly altered production patterns and social relations. Employing a social history approach, this study traces the dynamics of collective labor in the masambe tradition, social stratification based on land ownership and noble genealogical symbols (balailo), and the transformations brought by industrial technology and the younger generation’s economic orientation. The findings indicate that sago ownership has long been closely tied to social status and symbolic capital, while technological and market developments have produced new forms of stratification rooted in capital ownership. Nevertheless, collective values endure through sumambe rama (mutual cooperation) practices that sustain internal solidarity. This study highlights that shifts in the To Limola social structure are driven not merely by economic factors but by the complex interplay between customary systems, agrarian politics, and modernization.